Annual Review of Nursing Research, 23 (2005) : Alcohol Use, Misuse, Abuse, and Dependence. - Fitzpatrick, Joyce J. (Springer Pub. Co., 2005)
Designated a Doody's Core Title!. This volume brings together, for the first time, all the research on alcohol use that is relevant to nursing practice. Alcohol plays a major role in health care problems, which affects nursing practice from obstetrics to geriatrics. It also may have some significant health benefits, when used in moderation. This book reviews the research on both detrimental and beneficial effects, throughout the lifespan. As in all the Annual Reviews, leading nurse researchers provide students, researchers, and clinicians with the foundations for evidence-based practice and fu.